MANAJEMEN PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA PADA SEKSI PENYULUHAN AGAMA ISLAM KANWIL KEMENTERIAN AGAMA D.I. YOGYAKARTA - Abdulloh Muhamad Al-Kaff; Karwadi; Nadilla Aleyda Maqhfira Agustin; Nur Ahmad Ghojali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of human resource competency development in the Islamic Religious Extension Section of the Regional Office of the Ministry of Religious Affairs of the Special Region of Yogyakarta from the perspective of Islamic Education Management. The study used a descriptive qualitative approach with a case study design based on internship activities, institutional observation, document review, and focused interviews with elements of the apparatus and Islamic religious instructors. Data analysis was conducted through data reduction, thematic presentation, interpretation, and drawing conclusions. The results show that the development of extension worker competencies has been directed at technical, managerial, socio-cultural, and digital competencies. However, pedagogical competencies as community educators have not been fully formulated explicitly in the planning, mentoring, and impact evaluation cycle. This article offers a P3E-D model consisting of needs mapping, competency strengthening, educational mentoring, impact evaluation, and knowledge digitization. This model strengthens the position of extension workers as human resources in community-based non-formal Islamic education.